The Passing of Protestant England: Secularisation and Social Change c. 1920–1960 - McCabe, Michael (A journal of church and state, 2011)
Secularization in twentieth-century Britain is a topic that continues to fascinate both historians and sociologists. While most scholars have no difficulty agreeing that Britain was a de facto secular nation from the 1960s, the first half of the century continues to present fertile ground for debate. With his newest book, S. J. D. Green revisits the “secularization theory,” challenging the findings of revisionists who argue that there were varying degrees of Christian revival at mid-century.